2017
DOI: 10.1007/s11605-017-3397-y
|View full text |Cite
|
Sign up to set email alerts
|

Parenchymal-Sparing Versus Anatomic Liver Resection for Colorectal Liver Metastases: a Systematic Review

Abstract: PSH had a comparable safety and efficacy profile compared with AR and did not compromise oncologic outcomes. PSH should be considered an appropriate surgical approach to treatment for patients with CLM that facilitates preservation of hepatic parenchyma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
82
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 45 publications
2
82
1
4
Order By: Relevance
“…The total score is based on six difficulty indices: tumor location (score ranging from 1-5); extent of hepatic resection (score, 0-4), tumor size (score, 0 or 1-3 cm is used as the cutting point), proximity to major vessel (score, 0 or 1-"yes or no"); liver function (score, 0 or 1, determined by the Child-Pugh Score), and if it is a hand-assisted or hybrid procedure (score, 0 or 1). The 12 difficulty levels were divided into four categories (4-level difficulty), as follows: low (0-3), intermediate (4)(5)(6), advanced (7)(8)(9), and expert difficulty (10-12) (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The total score is based on six difficulty indices: tumor location (score ranging from 1-5); extent of hepatic resection (score, 0-4), tumor size (score, 0 or 1-3 cm is used as the cutting point), proximity to major vessel (score, 0 or 1-"yes or no"); liver function (score, 0 or 1, determined by the Child-Pugh Score), and if it is a hand-assisted or hybrid procedure (score, 0 or 1). The 12 difficulty levels were divided into four categories (4-level difficulty), as follows: low (0-3), intermediate (4)(5)(6), advanced (7)(8)(9), and expert difficulty (10-12) (9).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding both the learning curve and clinical practice, posterosuperior (PS) segments have been considered a challenging procedure by laparoscopy . The goal of parenchymal‐sparing for lesions into these segments is hardly achieved by laparoscopy, and it could be a drawback for patients with CRLM that generally requires more liver sparing procedures for eventual re‐hepactetomies for liver recurrence …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the early days of liver surgery for CRLM, when wide resection margins were considered a prerequisite for curative resection, it had been shown that decreasing margin size, does not compromise the oncologic effect of surgery . At the same time, it had been demonstrated that anatomic resection had no benefit over smaller, nonanatomic resection in CRLM, and that parenchymal sparing had paramount importance, both to increase safety, and “keep the door open” for future resections . Although these trends‐ small margins, nonanatomic resections and parenchymal sparing‐ did not result in compromised oncological outcomes, the benefit as well as impact of R1 resection on disease progression, control of liver disease and OS is less clear, and is difficult to assess, given the paucity of prospective data on the matter.…”
Section: Discussionmentioning
confidence: 99%
“…9 At the same time, it had been demonstrated that anatomic resection had no benefit over smaller, nonanatomic resection in CRLM, and that parenchymal sparing had paramount importance, both to increase safety, and "keep the door open" for future resections. 22 Although these trends-small margins, nonanatomic resections and parenchymal sparing-did not result in compromised oncological outcomes, [22][23][24] the benefit as well as impact of R1 resection on disease progression, control of liver disease and OS is less clear, and is difficult to assess, given the paucity of prospective data on the matter. resections, indicates that R1 resection may be worth pursuing, whenever an R0 is not feasible, and the surgical risk is acceptable.…”
Section: Discussionmentioning
confidence: 99%